2021
DOI: 10.1177/2515690x211006333
|View full text |Cite
|
Sign up to set email alerts
|

Cassia Abbreviata Enhances Glucose Uptake and Glucose Transporter 4 Translocation in C2C12 Mouse Skeletal Muscle Cells

Abstract: Background. This study aim at assessing C. abbreviata aqueous extracts for its potential to exhibit anti-diabetic activity in skeletal muscle cells. In addition to the toxicological and glucose absorption studies, the action of C. abbreviata extracts on some major genes involved in the insulin signaling pathway was established. Methods. The in vitro cytotoxic effects C. abbreviata was evaluated on muscle cells using the MTT assay and the in vitro glucose uptake assay conducted using a modified glucose oxidase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Studies have shown a reduction in IRS-1 and GLUT4 gene expression in skeletal muscle in T2DM patients [14,15]. Some plant extracts have been shown to increase IRS1 expression, resulting in enhanced insulin-stimulated glucose uptake and reduced hyperglycaemia [16,17]. Similarly, agents that upregulate GLUT4 gene expression enhance insulinstimulated glucose transport, corrects IR, and improves glycaemic control in diabetes [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown a reduction in IRS-1 and GLUT4 gene expression in skeletal muscle in T2DM patients [14,15]. Some plant extracts have been shown to increase IRS1 expression, resulting in enhanced insulin-stimulated glucose uptake and reduced hyperglycaemia [16,17]. Similarly, agents that upregulate GLUT4 gene expression enhance insulinstimulated glucose transport, corrects IR, and improves glycaemic control in diabetes [17][18][19].…”
Section: Resultsmentioning
confidence: 99%
“…Real-time (RT) qPCR showed an increased expression of GLUT4, IRS1 (insulin receptor substrate 1) and PI3K (phosphoinositide 3-kinase) in cells treated with bark extract (Kamga-Simo et al, 2021). A study by (Shai et al, 2010) showed that acetone extracts of Cassia abbreviata Oliv.…”
Section: Cassia Abbreviata Olivmentioning
confidence: 99%
“…Here we summarize some of the recent studies that show its potential to act as an antidiabetic medicinal plant. ( Kamga-Simo et al, 2021 ) assessed the potential of Cassia abbreviata Oliv. aqueous extracts to function as an antidiabetic agent on skeletal muscle cells and showed that the aqueous concoction enhanced glucose uptake and induced a two-fold increase in glucose transporter 4 (GLUT4) translocation in C2C12 mouse skeletal muscle cells.…”
Section: Medicinal Plants In Zimbabwe With Antidiabetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…C. abbreviata has been used in many parts of Africa as a traditional medicine for the treatment of various illnesses, including diabetes mellitus, constipation, headache, diarrhea, skin diseases, fever, infertility, cough, bilharzia, syphilis, malaria and jaundice [16,17]. In Tanzania, a decoction of the root is used for abdominal pains, dysentery, fever, malaria, hernia, wounds, syphilis, impotency, and snake bites [18].…”
Section: Introductionmentioning
confidence: 99%